2013
DOI: 10.1080/19371918.2013.774668
|View full text |Cite
|
Sign up to set email alerts
|

Just Say Know: An Examination of Substance Use Disorders among Older Adults in Gerontological and Substance Abuse Journals

Abstract: This article examines the extent to which studies of alcohol abuse, illicit drug use, and prescription drug abuse among older adults appear in the leading gerontological and substance abuse journals. The authors reviewed articles published in the 10 social science gerontological journals and the 10 social science substance abuse journals with the highest 5-year impact factors in PubMed from 2000 to 2010. Articles were selected that presented original research on alcohol, substance, or prescription abuse with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…8,14-16 To date, no nationally representative studies have examined variations in the use of opioids in older adults and how the use was associated with state regulations. 5,17-18 To address this gap in knowledge, we use 2007-2012 national data of Medicare beneficiaries to investigate this escalating public health issue. Understanding multilevel factors associated with opioid use and outcomes in older adults and the impact of policy will offer important insights into developing guidelines for safe and effective use of opioids in this population.…”
Section: Introductionmentioning
confidence: 99%
“…8,14-16 To date, no nationally representative studies have examined variations in the use of opioids in older adults and how the use was associated with state regulations. 5,17-18 To address this gap in knowledge, we use 2007-2012 national data of Medicare beneficiaries to investigate this escalating public health issue. Understanding multilevel factors associated with opioid use and outcomes in older adults and the impact of policy will offer important insights into developing guidelines for safe and effective use of opioids in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Although not a particularly high-risk group the higher rates of DPD in women than men in the 65+ age group in all but 3 western states suggests greater research and education is needed for the elderly about DPD. In reviewing literature on substance abuse among those >50, Rosen et al (2013) found that only 1% of articles in the top ten gerontology and substance abuse journals addressed substance abuse in the >50s. This is a research gap that needs addressing.…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…Studies also show that there is lack of focus on the elevated use of alcohol and psychotropic drugs when healthcare personnel and GPs apply for or facilitate services for older people (Duckert, Lossius, Ravndal, & Sandvik, 2008;Johannessen, Engedal, & Helvik, 2014;Johannessen, Helvik, Engedal, Ulstein, & Sørlie, 2015;Sandvik, 2014). A review study indicates that there has been little research addressing substance abuse in older adults (Rosen, Engel, Hunsaker, Engel, & Reynolds, 2013). What is more, studies examining the differences and similarities between referral sources and selfreported use of alcohol and psychotropic drugs, as well as the reasons for these differences, are not well documented (Helseth, Lykke-Enger, Aamot, & Johnsen, 2005;Høiseth et al, 2013).…”
mentioning
confidence: 99%